2016
DOI: 10.1063/1.4963307
|View full text |Cite
|
Sign up to set email alerts
|

A new system for continuous and remote monitoring of patients receiving home mechanical ventilation

Abstract: Home mechanical ventilation is the treatment of patients with respiratory failure or insufficiency by means of a mechanical ventilator at a patient's home. In order to allow remote patient monitoring, several tele-monitoring systems have been introduced in the last few years. However, most of them usually do not allow real-time services, as they have their own proprietary communication protocol implemented and some ventilation parameters are not always measured. Moreover, they monitor only some breaths during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…When one gets older, they breathe weaker, and their number of breaths per minute (the respiratory rate) increases. This finding is consistent with those reported in previous works [21][22][23][24][25][26][27]. It is also worth noting in Figure 2a-c that the breath amplitude, which is proportional to the change in impedance due to breathing (defined as ∆Z = Z h − Z l ), of subject 2 is significantly lower than those of the other two (subjects 1 and 3).…”
Section: Real-time Monitoring Of Human Respiratory Motion At Different Agessupporting
confidence: 92%
See 1 more Smart Citation
“…When one gets older, they breathe weaker, and their number of breaths per minute (the respiratory rate) increases. This finding is consistent with those reported in previous works [21][22][23][24][25][26][27]. It is also worth noting in Figure 2a-c that the breath amplitude, which is proportional to the change in impedance due to breathing (defined as ∆Z = Z h − Z l ), of subject 2 is significantly lower than those of the other two (subjects 1 and 3).…”
Section: Real-time Monitoring Of Human Respiratory Motion At Different Agessupporting
confidence: 92%
“…Research has shown that respiratory rate varies considerably with age [21][22][23][24][25][26][27]. For instance, an infant (1-12 moths) breathes between 30 and 60 times per minute, toddlers (1-2 years) breathe anywhere from 24 to 40 times per minute, and preschoolers (3-5 years) breathe between 22 and 34 times per minute.…”
Section: Real-time Monitoring Of Human Respiratory Motion At Different Agesmentioning
confidence: 99%
“…The lack of real-time monitoring and data processing remains a limitation for bedside application. Battista developed a remote system to monitor home-based ventilation therapy, enabling close monitoring of therapy in remote locations [41]. This system can simultaneously observe different remote therapy units and users were able to detect multiple clinical events.…”
Section: Related Workmentioning
confidence: 99%
“…Unfortunately, many cases were due to a preventable complication rather than the progression of underlying disease, and highest in low‐income areas 44,89,91 . Safety may be improved by use of in‐home telemedicine and, potentially, remote monitoring 92‐94 …”
Section: Discharge and Outpatient Care With Chronic Ventilationmentioning
confidence: 99%